Aeolian silt contribution to soils on mountain slopes (Mt. Ślęża, southwest Poland). Issue 3 (23rd October 2017) - Waroszewski, Jaroslaw; Sprafke, Tobias; Kabala, Cezary; Musztyfaga, Elżbieta; Łabaz, Beata; Woźniczka, Przemysław
Abstract: This paper evaluates the possible contribution of aeolian silt to soils of Mt. Ślęża (southwest Poland). Silt loam textures are common across Lower Silesia and are often confused with silt clay loam, especially at the outer boundaries with thin loess deposits. Eight study sites with different thicknesses of silt loam mantles that are covered and/or mixed with underlying sediments were examined in the field. To test our hypothesis, we analyzed the particle size and geochemistry of representative horizons. Concentrations of major and trace elements as well as their cross ratios confirmed the aeolian origin of silt loam materials and clearly distinguished them from basal sediments. There is a clear relationship between the presence and depth of aeolian mantles and mixing zones with the type of underlying material. Furthermore, the incorporation of aeolian silt to regoliths/soils was a main agent initiating and stimulating clay translocation leading to the formation of an argic horizon below the silt mantles. Mixing aeolian silt with acid granite regoliths and further illuviation resulted in the formation of alisols, while silt contributions to serpentine sediments resulted in development of skeletic luvisols. Soils receiving very weak input of aeolian silts remain as leptosols/cambisols.